2022
DOI: 10.3389/fonc.2022.963364
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing identified a novel POT1 variant as a candidate pathogenic allele underlying a Li–Fraumeni-like family

Abstract: BackgroundLi-Fraumeni syndrome (LFS) and Li-Fraumeni-like (LFL) syndrome are rare hereditary diseases characterized by predisposition to a diverse spectrum of cancer types, primarily sarcoma. The pathogenic variants underlying the majority of LFL cases remain to be explored.MethodsWe performed whole-exome sequencing (WES) on 13 core members of a large LFL family with highly aggregated incidences of cancers, including cases with sarcoma, non-small cell lung cancer and cardiac angiosarcoma, and conducted a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…On a side note, a WES study identified the p.P35L variant in one out of 13 probands of LFL families. The variant is not reported in any database, and its pathogenicity is predicted by in silico structural analysis [20].…”
Section: Sarcomamentioning
confidence: 99%
“…On a side note, a WES study identified the p.P35L variant in one out of 13 probands of LFL families. The variant is not reported in any database, and its pathogenicity is predicted by in silico structural analysis [20].…”
Section: Sarcomamentioning
confidence: 99%